Effects of Training Opportunities on Employees’ Career Development at Moshi Municipal Council, Tanzania - Ntinda, Prisca Fredrick; Onyancha , Hezron; Amembah, A. Lamu Amos (Universitas Nahdlatul Ulama Surabaya, 2025)
This study assessed the effects of training opportunities on employees’ career development: a case of Moshi municipal council Tanzania. This study employed a convergent mixed-methods design under the mixed research methods approach. The target population comprised 325 employees across nine departments at Moshi Municipal Council. The sample size for the study was determined using Yamane’s (1967) formula and got 179 respondents. The study utilized simple random sampling and purposive sampling to obtained respondents. Data were collected using structured questionnaires for employees and interview guides for the Heads of Departments. The reliability of the instruments was verified using Cronbach’s Alpha and got 0.87 for the questionnaires while peer debriefing for qualitative instruments was ensured. Quantitative data were analyzed descriptively such as frequencies, percentages, means and standard deviation with aid of SPSS version 22, while qualitative data were analyzed by using contextual analysis, supported by direct quotations from participants. Ethical considerations such as voluntary participation, anonymity, and proper academic citation were observed. The study was guided by Herzberg’s Motivation-Hygiene Theory. The study revealed that training opportunities at Moshi Municipal Council are perceived to have a high extent of influence on employees’ career development. The study concludes that training is a crucial driver of career development within Moshi Municipal Council. It is recommended that Moshi Municipal Council implement regular, inclusive, and need-based training programs aligned with both employee and organizational goals. The council should also improve training access, allocate more resources, and establish follow-up mechanisms to ensure practical application and impact.